Web-Based Sales Information System Design in Small and Medium Enterprises - D Effendi; S Saepullah; M I Rismaya (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this research is to create a website-based information system design for Small and Medium Enterprises (SMEs) to help them facilitate their business in the field of technology. This research was conducted using descriptive qualitative methods with literature study based on various studies that has been done, and used object-oriented approaches as system builder, the development method used prototype method. The results obtained from this study are an information system design that can facilitate SMEs in terms of sales and promotion. The conclusion is that the information system website could be able to help SMEs to develop their business in terms of promotion and sales so that they can compete with large companies. The ability of information systems can add new opportunities or opportunities for SMEs to expand their market share at affordable costs.